2020
DOI: 10.1002/ardp.202000223
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4‐Triazole hybrids with potential antibacterial activity against methicillin‐resistant Staphylococcus aureus

Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) has developed numerous mechanisms of virulence and strategies to evade the human immune system, and it can be transmitted between humans, animals, and the environment. Thus, MRSA is an important cause of morbidity and mortality in both hospitals and in the community, creating an urgent demand for the development of novel anti‐MRSA candidates. The 1,2,4‐triazole nucleus is a bioisostere of amide, ester, and carboxylic acid, and the 1,2,4‐triazole ring is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 82 publications
0
9
0
2
Order By: Relevance
“…Numerous heterocycles containing [1,2,4]-triazole units have previously demonstrated promising antibacterial activity through inhibition of bacterial DNA gyrase, which is a key enzyme involved in bacterial replication. Consequently, we reasoned that our triazolobenzoazepinium salts 5 might also be exhibiting their antibacterial activity in a similar manner and so decided to carry out in silico screening studies to determine their ability to inhibit DNA gyrase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Numerous heterocycles containing [1,2,4]-triazole units have previously demonstrated promising antibacterial activity through inhibition of bacterial DNA gyrase, which is a key enzyme involved in bacterial replication. Consequently, we reasoned that our triazolobenzoazepinium salts 5 might also be exhibiting their antibacterial activity in a similar manner and so decided to carry out in silico screening studies to determine their ability to inhibit DNA gyrase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Lucrarea a fost realizată în cadrul proiectelor "Cercetări complexe de elaborare a noilor produse farmaceutice antiinfecțioase autohtone pentru optimizarea farmacoterapiei afecțiunilor stomatologice, orofaringiene și auriculare" cifru 20.80009.8007. 14…”
Section: Rezumatunclassified
“…Este demonstrat faptul, că derivații de 1,2,4-triazol posedă activități anti-bacteriene promițătoare atât împotriva bacteriilor sensibile la medicamente, cât și a celor rezistente la medicamente [13]. Derivații de 1,2,4-triazol au capacitatea de a exercita activitatea lor antibacteriană prin inhibarea pompelor de eflux, a AND-girazei și topoizomerazei IV și joacă un rol important în descoperirea de noi agenți antibacterieni [14].…”
unclassified
“…Literature data concluded that, fused heteroaromatic system exhibited excellent biological activity like N-alkyl-6-nitro-3,5-dihydro [1,2,4]triazolo [1,5-a]pyrimidin-7-amine, [1,2,4]triazolo [1,5-c]pyrimidines exhibited anticonvulsant and antiparasitic activity, respectively, as shown in Figure 1. [1] Among the heterocyclic systems, 1,2,4-triazole and its derivatives attracted synthetic and medicinal chemist due to various pharmacological potential like anxiolytic, [2][3][4][5] antibacterial, [6][7][8][9] anti-parasitic, [10] antiviral, [11] anti-oxidant, [12] fungicide, [13][14][15] antituberculosis, [16] antiepileptic, [17] antitumor. [18 -20] 1,2,4triazoles are derived from pyrazole via substituting doi.org/10.1002/cbdv.202200679 carbon by nitrogen atom at position 4, it acts as isosteres of ester, amide and carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%